Non-native and Invasive Nylanderia Crazy Ants (Hymenoptera: Formicidae) of the World: Integrating Genomics to Enhance Taxonomic Preparedness. (16th March 2020) - Williams, Jason L; Lucky, Andrea
Abstract: Invasive species have devastating economic and ecological impacts worldwide, but proactive monitoring programs are rare on the global stage. By definition, tramp ants are associated with disturbance and human-mediated dispersal, making them especially concerning invasive threats. A proactive—rather than reactive—approach to monitoring for, preventing, and managing invasive species depends on taxonomic preparedness, which enables rapid and accurate identification. Emerging tools and technologies, including genomic barcoding and interactive online keys, can aid in species delimitation and diagnosis. However, resolving tramp species' identities remains the fundamental first step in invasive species management because diagnostic tools cannot be developed and disseminated until species names are stable. Diagnosis of morphologically difficult species requires basic knowledge of species boundaries, biogeography, and phylogenetic relationships. This review comprehensively synthesizes information available for 15 known and five potential tramp ant species in Nylanderia (Emery) (Hymenoptera: Formicidae): a globally distributed genus of over 130 described species, many of which are only diagnosable by subtle morphological characters. Nylanderia records were drawn from published literature, specimen databases, and museum collections to compile known distributions, biology, natural history, and taxonomy for each species. We review existing resources for visualizing known geographic ranges and high-resolution images of ants globally and encourage the use of these types of tools in support of invasive species diagnosis and distribution tracking. Finally, we discuss how taxonomic and life history information can be used synergistically with genomic and digital technology to develop tools for identification of these, and other emerging invasive insect species.